Care Management of Bicuspid Aortic Valve Regurgitation: Competencies of a Mother as an Advanced Practice Nursing Faculty - ธงชัย, ฉวีวรรณ (Thai Journal of Nursing and Midwifery Practice, 2019)
Abstract: Bicuspid aortic valve disease roughly affects 1 to 2 % of the population. Fifty percents of bicuspid aortic valve disease can lead to aortic dilation which can lead to rupture of the vessel or aortic dissection. Patients frequently require surgical treatment to prevent the development of aortic regurgitation and aortic aneurysm. Aotic valve repaired becomes an alternative to replacement of bicuspid aortic valves. This case study was a 31 years old man, a professional golfer, whose mother was a critical care advanced practice nursing faculty. This article presents the case study, knowledge related to the bicuspid aortic valve disease and the operation done by the world famous surgeonon heart and cardiovascular from Germany. It also demonstrates the competencies of the mother, as a critical care advanced practice nursing faculty in managing the care of her son during the complex illness situations.